Regularity of Filitration Properties Distribution in Oil Bearing Reservoir with Complex Geological Structure - Merkulov V. P. Vitaly Pavlovich; Krasnoshchekova L. A. Lubov Afanasievna; Korovin M. O. Mikhail Olegovich; Cherdantseva D. A. (2016, 2016)
Title screen